2014
DOI: 10.1111/ggi.12348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frailty among Japanese, Brazilian Japanese descendants and Brazilian community‐dwelling older women

Abstract: The older Brazilian women were likely to be more frail than the participants in other groups. More than the environment itself, the lifestyle and sociodemographic conditions could affect the frailty of older Brazilian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…We identified that the majority of authors maintained the Japanese term "Kihon Checklist" 11,15,17,20,21 or used similar terms, "Kihon-Checklist" 22 and "Kihon Check Lists." 12 In addition, some authors translated and denominated the checklist as "Basic checklist for frailty"; 23 "Basic questionnaire" and "basic checklist";…”
Section: Kcl Terminologymentioning
confidence: 99%
See 4 more Smart Citations
“…We identified that the majority of authors maintained the Japanese term "Kihon Checklist" 11,15,17,20,21 or used similar terms, "Kihon-Checklist" 22 and "Kihon Check Lists." 12 In addition, some authors translated and denominated the checklist as "Basic checklist for frailty"; 23 "Basic questionnaire" and "basic checklist";…”
Section: Kcl Terminologymentioning
confidence: 99%
“…24 There is no consensus regarding the division of the KCL domains; some researchers considered the first domain of the KCL as the first five questions (naming it "instrumental activities of daily living -IADL"), 12,17,20,23 whereas others considered it as the sixth to tenth questions, for example. Although the majority of studies divided the domains as aforementioned, exceptions were observed.…”
Section: Kcl Terminologymentioning
confidence: 99%
See 3 more Smart Citations